Implementasi Link Fast-Failover Pada Multipath Routing Jaringan Software-Defined Network - Muhammad Aji Wibowo; Widhi Yahya; Dany Primanita Kartikasari (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Software-defined network is a concept of computer network approach where the control plane is separated by data plane. The communication between the data plane controller uses the OpenFlow protocol. In an SDN architecture it often happens to have interference such as failure link. in the latest openflow protocol there is a group type that overcomes the interruption of the link is using a fast-failover mechanism. Tests conducted to measure the performance of the system include testing functionality, response time and packet loss. The results of the test obtained from this study are able to search the path at the time before the link down and after the link down. At the time of link 1 in down in topology has a response time with an average of 0.38-0.681 ms and in link 2 has an average of 0.272 - 0.549 ms. When the link is down, the lost packet until it finds the new path can be known the value of packet loss. packet loss obtained from the simulation has an average of 0.423% -0.636%.